Total Quality Management Practices and it’s reflection on Innovation Empirical research in Middle East Bank for Investment - عبد الوهاب نادية لطفي; عبد الجبار انفال عبد الستار (Journal of Economics and Administrative Sciences, 2017)
This research aims to assess the adoption of TQM in the Middle East Bank for Investment, and diagnosis means and techniques of technological innovation that applied in, as well as to determine the nature of the relationship between total quality management practices (operations management, employment relations, customer relations) and technological innovation (the incremental innovation of the service, incremental innovation process, a radical innovation of the service, a radical innovation of the operation), through use the checklists, derived from a study (Kim et al, 2012) the many styles of mathematical and statistical tools was adopted like the percentage, mean, duplicates, as well as the adoption of the Z test that shows whether there is a reflection of the total quality management practices in technological innovation management. Research has found that the management of the bank was able to employ a set of comprehensive quality management practices and benefit from the introduction of new technology or the development and improvement of the technology used to understand, accomplish and facilitate the work of the bank more efficiently. And it included a number of recommendations, including the bank manage employee training on quality program to promote awareness about the concepts and principles of total quality management and publishing quality culture through specialized publications as well as the organization of conferences and seminars on total quality management, as well as exploit the intellectual capital in the bank, through the employment knowledge, skills, experiences to launch activating the creative intellectual energy and make it a strategic necessity.